Broad Phenotypes of Disorders/Differences of Sex Development in MAMLD1 Patients Through Oligogenic Disease - Flück, Christa E.; Audí, Laura; Fernández-Cancio, Mónica; Sauter, Kay-Sara; Martinez de LaPiscina, Idoia; Castaño, Luis; Esteva, Isabel; Camats, Núria (Frontiers in Genetics, 2019)
Disorders/differences of sex development (DSD) are the result of a discordance between chromosomal, gonadal and genital sex. DSD may be due to mutations in any of the genes involved in sex determination and development in general, as well as gonadal and/or genital development specifically. MAMLD1 is one of the recognized DSD genes. However, its role is controversial as some MAMLD1 variants are present in normal individuals, several MAMLD1 mutations have wild-type activity in functional studies, and the Mamld1-knockout male mouse presents with normal genitalia and reproduction. We previously tested 9 MAMLD1 variants detected in nine 46,XY DSD patients with broad phenotypes for their functional activity, but none of the mutants, except truncated L210X, had diminished transcriptional activity on known target promoters CYP17A1 and HES3. In addition, protein expression of MAMLD1 variants was similar to wild-type, except for the truncated L210X. We hypothesized that MAMLD1 variants may not be sufficient to explain the phenotype in 46,XY DSD individuals, and that further genetic studies should be performed to search for additional hits explaining the broad phenotypes. We therefore performed whole exome sequencing (WES) in seven of these 46,XY patients with DSD and in one 46,XX patient with ovarian insufficiency, who all carried MAMLD1 variants. WES data were filtered by an algorithm including disease-tailored lists of MAMLD1-related and DSD-related genes. Fifty-five potentially deleterious variants in 41 genes were identified; 17/55 variants were reported in genes in association with hypospadias, 8/55 with cryptorchidism, 5/55 with micropenis, and 13/55 were described in relation with female sex development. Patients carried 1-16 variants in 1-16 genes together with their MAMLD1 variation. Network analysis of the identified genes revealed that 23 genes presented gene/protein interactions with MAMLD1. Thus, our study shows that the broad phenotypes of individual DSD might involve multiple genetic variations contributing towards the complex network of sexual development.